Frailty and the role of nutrition in older people A review of the current literature - Kaiser, Matthias J.; Bandinelli, Stefania; Lunenfeld, Bruno (Acta Biomedica Atenei Parmensis, 2010)
Frailty and malnutrition are both highly prevalent in the older population and have therefore become principle topics in geriatric research. Frailty is of multifactorial origin and is regarded as a fundamental risk factor for deteriorating health status and disability in older people. It is estimated that prevalence rates for frailty and pre-frailty reach as high as 27% and 51%, respectively. The role of nutritional deficiency in the development of frailty was suggested long ago, however research conducted in this area is relatively recent. The critical role of micronutrients in this context suggests the need to improve the quality of food eaten by older people – not just the quantity. This review summarizes the recent literature on the nutritional pathways to frailty with particular focus on the effect of energy, protein and micronutrients.